Factors Influencing Student’s Books Buying Behavior In Malaysia Higher Learning Institutions - Teh, Teik Lee (2004)
The growing importance of higher education (Mahdzan & Fauziah, 1999) with the rapid growth of student enrollments is expected to increase the textbooks purchase in higher education market. However, the textbook sales seem to be much lower than the expected. This study undertakes to explore the current level and patterns of textbook purchase and the influence of external market factors on student’s books buying in public and private institutions in Malaysia. The theoretical framework adapted from Cohen’s (1991) buying decision process model proposed hypotheses to assess the relationship between the 4Ps and substitutions and the books purchased.